2017
DOI: 10.3390/app7010085
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Iron and Selenium Uptake in Plants by Volatile Emissions of Bacillus amyloliquefaciens (BF06)

Abstract: Volatile organic compounds (VOCs) released by plant growth-promoting rhizobacteria (PGPR) are involved in promoting growth and triggering systemic resistance (ISR) in plants. Importantly, the release of VOCs by some PGPR strains confers improved plant uptake of nutrient elements from the soil. However, the underlying mechanisms of VOCs-regulated nutrient acquisition remain elusive. In this study, VOCs were extracted and identified from Bacillus amyloliquefaciens (strain BF06) using gas chromatography-mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 74 publications
(96 reference statements)
1
25
1
Order By: Relevance
“…In nature, soil-borne bacteria can emit diverse kinds of VOCs for overcoming physical constraints of soil matters to reach plant roots, even aboveground tissues of plants, thereby affecting various physiological processes in plants [ 21 ]. It has recently been shown that the production of VOCs by PGPR strains can regulate Fe and selenium (Se) absorption, photosynthesis, and pathogen invasion [ 31 , 32 , 33 , 34 ]. However, whether microbial VOCs induce Cd tolerance of pants and the underlying mechanisms are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In nature, soil-borne bacteria can emit diverse kinds of VOCs for overcoming physical constraints of soil matters to reach plant roots, even aboveground tissues of plants, thereby affecting various physiological processes in plants [ 21 ]. It has recently been shown that the production of VOCs by PGPR strains can regulate Fe and selenium (Se) absorption, photosynthesis, and pathogen invasion [ 31 , 32 , 33 , 34 ]. However, whether microbial VOCs induce Cd tolerance of pants and the underlying mechanisms are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An aliquot of 30 μL of bacterial culture was used to expose plants to VOCs according to the method described by Asari et al [ 40 ]. Moreover, the production of VOCs by SAY09 was identified using gas chromatography (GC)–mass spectrometry (MS) analyses as reported recently by Wang et al [ 34 ].…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Selenium is known to accumulate in crops grown on soils with high selenium content [161,189], and selenium enrichment has been reported in soils throughout the United States [190]. In their recent study, Wang et al [191] found that volatile organic compounds released by plant growth-promoting rhizobacteria increases both selenium and iron uptake. Uranium is another geogenic, potentially toxic contaminant [192] and studies in nutrient culture show its uptake by crops [193,194].…”
Section: Geogenic Contaminants In Irrigation Watermentioning
confidence: 99%